An Analysis of Loan Sanctioning System Applying in Various Agriculture Development Banks of Asian Countries: A Calculative Approach of Nepalese Farming Sector - Karna, Santosh Kumar; Sahani, Suresh Kumar (MANAZHIM, 2024)
In this research paper, we have studied the role of Agriculture Development Banks especially in terms of loan sanctioning to farmers in asian countries with reference to Madhesh Province of Nepal. Also we study the condition of remmittance in this area for economic development of our country. This paper is showing in what way nepalese farmers are being affected with contingent liabilities and how as a borrower their numbers are increasing day by day.